Textural Characteristics and Energetic Parameters of Activated Carbon Monoliths: Experiments and Monte Carlo Simulations - Diana P. Vargas; J.C. Alexandre de Oliveira; Liliana Giraldo; Juan Carlos Moreno-Piraján; R.H. López; G. Zgrablich (Adsorption Science & Technology)
Disc-type activated carbon monoliths were prepared through chemical activation of coconut shell and African palm pits with phosphoric acid at different concentrations, without using any binder. The structures thereby produced were studied experimentally by nitrogen adsorption at 77 K, carbon dioxide adsorption at 273 K and immersion calorimetry in benzene. The experimental data allowed the textural and energetic characterization of the microporous solids to be obtained, viz. BET areas between 752 and 1711 m 2 /g, micropore volumes between 0.32 and 0.61 cm 3 /g, ultramicropore volumes between 0.11 and 0.24 cm 3 /g and immersion enthalpy values between 95.85 and 147.7 J/g. Grand Canonical Monte Carlo (GCMC) simulations were used to analyze the experimental results, providing an interpretation of, as well as a more detailed characterization, of the textural properties, such as the determination of the pore-size distribution (PSD) of each material.